1994
DOI: 10.1002/sia.740210303
|View full text |Cite
|
Sign up to set email alerts
|

Use of image depth profiling SIMS for the study of tinplate corrosion

Abstract: Four tinplate specimens with different corrosion properties were studied using secondary ion mass spectrometry (SIMS) image analysis. The continuity of the structure of the interfacial iron‐tin alloy was able to be examined using a volume rendition computer program, which generates a three‐dimensional representation of the stack of ion images. The surface coverage of tinplate was found to vary widely on some specimens; those exhibiting poor corrosion characteristics were found to have little or no elemental ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 2 publications
0
12
0
Order By: Relevance
“…5,12 The tin coating exhibits locally signicant differences in thickness depending on surface topography of the base steel. 2,15 Another crucial point is the possible presence of defects such as porosity in the tin layer or the alloy layer. 2,6,16 Previous studies 5,15 by means of secondary ion mass spectroscopy analyses have revealed the exposure of Fe-Sn alloy or the base steel through pores on the tinplate, that will cause severe corrosion during storage in humid conditions or usage in food cans.…”
Section: Introductionmentioning
confidence: 99%
“…5,12 The tin coating exhibits locally signicant differences in thickness depending on surface topography of the base steel. 2,15 Another crucial point is the possible presence of defects such as porosity in the tin layer or the alloy layer. 2,6,16 Previous studies 5,15 by means of secondary ion mass spectroscopy analyses have revealed the exposure of Fe-Sn alloy or the base steel through pores on the tinplate, that will cause severe corrosion during storage in humid conditions or usage in food cans.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, during flow melting, the liquid tin in principle is expected to flow from the surface peaks to the depressions and, as consequence, the final tin layer can exhibit locally significant differences in thickness depending on surface topography of the substrate. Dynamic secondary ion mass spectroscopy investigations of commercial tinplate materials gave some evidence that the tin layer can be significantly thinner on rolling marks compared with the average thickness. Another crucial point is the possible presence of defects such as porosity or cracks in the tin layer that favour dramatically the corrosion of the substrate.…”
Section: Introductionmentioning
confidence: 99%
“…Another crucial point is the possible presence of defects such as porosity or cracks in the tin layer that favour dramatically the corrosion of the substrate. Indeed, secondary ion mass spectroscopy analyses of tinplate material revealed the presence of iron at the outermost surface thus indicating possible local exposition of the steel substrate through pores, cracks, or other defects. Note however, that diffusion of iron from the substrate into the tin film can occur to a significant extent even by a short heat treatment as typically carried out in industrial production of tinplate.…”
Section: Introductionmentioning
confidence: 99%
“…[25] Slices can then be reconstructed into a three-dimensional volume with approximate lateral resolutions as low as 100 nm and an approximate vertical resolution of 20 nm. [26][27][28][29]30,31,32] The FIB microscopes, using liquid metal ion sources, are particularly well suited to tomographic reconstructions because samples can be sectioned and data collected in the same chamber. A number of groups have used the technique to study many materials problems, and the remainder of this article will discuss the technique in detail.…”
Section: Comparison Of Tomographic Techniquesmentioning
confidence: 99%